EFFECT OF WEATHER TEMPERATURE ON FIRST IMPRESSION ABOUT ANOTHER PERSON - Martirosyan, D. M. (Modern Psychology, 2020)
This research study investigates the hypothesis that warmer external temperature leads to a more positive first impression of one’s emotion and personality. The study involved two groups of participants, one for each weather setting (cold and warm outside temperature). The participants were asked to fill in a google form questionnaire consisting of a consent form, basic information about their gender, age and nationality, POMS-A test to evaluate their mood at the time, personality and emotion assessment of two pictures (male and female), and a question about their weather preference. Four MANOVA models were constructed: one to test differences among emotions, and another – among personality traits for each picture. All models produced insignificant results (pvalue> 0.05), thus giving us insufficient evidence to reject the null hypothesis of external temperature having no effect on the formation of first impressions. After presenting the findings, potential reasons for obtaining such results are discussed.